2020
DOI: 10.1039/d0ra00556h
|View full text |Cite
|
Sign up to set email alerts
|

Silica-immobilized ionic liquid Brønsted acids as highly effective heterogeneous catalysts for the isomerization of n-heptane and n-octane

Abstract: Metal-free imidazolium-based ionic liquid (IL) Brønsted acids 1-methyl imidazolium hydrogen sulphate [HMIM]HSO4 and 1-methyl benzimidazolium hydrogen sulphate [HMBIM]HSO4 were synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These results showed that the three ILs were successfully prepared. 29,32,33 As shown in and $6% weight loss was found, which was mainly due to the evaporation of water. In the second stage from 82 C to 153 C, no signicant weight loss (<1%) was found.…”
Section: Il Characteristicsmentioning
confidence: 80%
“…These results showed that the three ILs were successfully prepared. 29,32,33 As shown in and $6% weight loss was found, which was mainly due to the evaporation of water. In the second stage from 82 C to 153 C, no signicant weight loss (<1%) was found.…”
Section: Il Characteristicsmentioning
confidence: 80%
“…In this regard, ILs have been anchored to the external surfaces and cavities of several porous solid material to place a thin layer of IL in order to make them more costeffective, easily recoverable, quicker diffusion and mass transfer. Up to now, silica [9,10], clays [11], organic polymers [12], zeolites [13] and metal oxides [14] are commonly used supports for the immobilization of ILs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the isolation of pure ILs from products and reusability has been the major issue in these processes in view of eco-sustainability. Therefore, the immobilization of these functionalized ILs over different solid supports to explore heterogeneous supported ILs has made the process easier through their easy handling, thermal stability, facile isolation and reusability [28][29][30][31][32][33]. Among these soild supports, mesoporous silica materials offer significant advantages of large surface area, highly ordered structure, thermal and chemical stabilities.…”
Section: Introductionmentioning
confidence: 99%